(3JYQjag, NWhGJg, efGgLg, GdeaGgje GdEMUGFjIs - (3CMeO YHO Gddg(B, (3GddMdMs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3GdYde hGdHMK GdYdej, CSGSjGJ GdefgL GdYdej aj GdHMK, COhGJ GdHMK GdYdejs
(3GdeQGLY U(B.300s
Keywords: (3CSGdjH GdHMKs; (3GdCSGdjH GdGMUGFjIs; (3GdHMK GdYdejs; (3GdefgLjIs